WE7.8 Neck of Femur Fractures with Co-existent History of Malignancy: Do Full-length Femur X-Rays Change Fixation Method?. (9th August 2022) - MacKinnon, Thomas; Ahmed, Mosab; Hashim, Sophia; Bhattacharya, Raj
Abstract: Introduction: In neck of femur (NOF) patients presenting with co-existent history of malignancy, it is regarded as good practice to obtain pre-operative full-length femur X-Rays (FLF-XRs) to identify metastatic disease distal to the fracture site and aid operative planning. Whether the availability of pre-operative FLF-XRs in the trauma meeting influences the surgeon's choice of fixation method between intramedullary nail (IMN) or dynamic hip screw (DHS), is unclear. Methods: We performed a retrospective analysis of all NOFs that underwent surgical fixation at a major London hospital over a 3-year period (2018–20), and collected data on history of any malignancy, FLF-XR status and fixation method (IMN vs DHS). Our results showed that of the 308 extracapsular NOFs during this time period, 23% had a history of malignancy, and of these, 55% had undergone FLF-XRs. NOFs with co-existent history of Ca who had undergone FLF-XR were more likely to undergo IMN fixation than DHS to a statistically significant degree (p<0.05) than those who did not, despite only 3% of these radiographs demonstrating distal femoral metastases. Results: The findings of this preliminary audit raise questions around the value of FLF-XRs in NOFs with co-existent malignancy, particularly if IMN fixation is opted for in the majority of cases despite normal radiographs. The next phase of this study is to establish whether IMN/DHS fixation, with or without pre-operative FLF-XRs, amongst this cohort correlate to better or worse complication rates.